A new species of the rare nematode genus Paramicrolaimus Wieser, 1954 (Chromadorida: Paramicrolaimidae) from the south eastern Arabian Sea - Jacob, Jini; Jaleel, Abdul K. U.; Vijayan, Anil Kumar (Zootaxa, 2015)
A new paramicrolaimid nematode, Paramicrolaimus damodarani sp. nov., is described based on specimens from the continental shelf (95 m) of the south eastern Arabian Sea. Paramicrolaimus damodarani sp. nov. differs from other known species of the genus in having a smaller body size, form of the spicular apparatus, presence of 7 cuticularised protruding precloacal supplements and a strongly cuticularised terminal spinneret. This is the first record of the genus Paramicrolaimus from the northern Indian Ocean. A pictorial key to the four species of Paramicrolaimus is also provided, supplemented with comparative characters, based on published information.